Interventions to reduce dehydration related to defunctioning loop ileostomy after low anterior resection in rectal cancer: a prospective cohort study. Issue 9 (24th August 2020) - Munshi, Eihab; Bengtsson, Eva; Blomberg, Karin; Syk, Ingvar; Buchwald, Pamela
Abstract : We demonstrated that a post‐operative surveillance programme was effective only to prevent symptomatic dehydration related to defunctioning loop ileostomy after low anterior resection in rectal cancer. The intake of diuretics and the elderly are at risk for dehydration and should be followed cautiously. Abstract: Background: Defunctioning loop ileostomy (DLI) in low anterior resection (LAR) in rectal cancer patients reduces the morbidity of anastomotic leakages. In our previous study, 30% of patients developed dehydration due to DLI, mostly during the first 6 weeks. This interventional study aimed to reduce these figures by establishing a surveillance programme. Methods: An interventional study of rectal cancer patients undergoing LAR and DLI between 2013 and 2015 was carried out. A historical study group was used as control. Stoma care nurses educated the intervention group about high‐output stoma. Blood tests, including creatinine and electrolytes, were taken every second week until 8 weeks post‐operatively and an additional control in case of subjective high‐output stoma. Results: Eighty‐seven patients underwent LAR and DLI during the study period. Twenty‐one (24%) developed dehydration episodes, and nine (43%) of them required readmission. There was no difference compared to the control group, where 29% developed dehydration, and about half (52%) needed readmission ( P = 0.62 and P = 0.57, respectively). However, when explicitly examining patients demonstrating symptomatic dehydration, there was a significant difference, that is 10 (11%) versus 27 (29%) ( P  < 0.005). Overall, the dehydrated group was older and more likely to take diuretics compared to the non‐dehydrated group. Conclusion: Our results indicate that reducing dehydration episodes and readmission after DLI is a challenging process. The proposed surveillance was only effective in preventing symptomatic dehydration. Subjects taking diuretics and the elderly are at risk of dehydration and should be followed cautiously.